POTENSI KULIT BATANG Cinnamomum burmannii Bl. DALAM MENCEGAH INFERTILITAS; KAJIAN TERHADAP BERAT TESTIS DAN JUMLAH SPERMATOZOA MENCIT (Mus musculus) MODEL DIABETES MELLITUS TIPE-1 - Moniharapon, Mechiavel; Ukratalo, Abdul M; Pattimura, Nadira; Samson, Efraim; Pangemanan, Victory O (Biofaal Journal, 2023)
In individuals with diabetes mellitus, the increase in Reactive Oxygen Species (ROS) can damage the mitochondrial membrane, leading to the loss of potential mitochondrial membrane function in inducing apoptosis of sperm cells. Cinnamomum burmannii is a type of spice that contains antioxidants, thus capable of neutralizing free radicals and reducing oxidative stress caused by diabetes mellitus. Flavonoids also have an effect on increasing spermatogenesis. The aim of this research is to examine the role of methanol extract from Cinnamomum burmannii bark in increasing testis weight and spermatozoa count in type-1 diabetes mellitus mice (Mus musculus). The study employs a Completely Randomized Design (CRD) with five treatments and three replications. Twenty mice are divided into groups: K- (control), K+ mice injected with STZ without medication), P1 (dose of 200 mg/kg BW), P2 (dose of 400 mg/kg BW), and P3 (dose of 800 mg/kg BW). Before administering the Cinnamomum burmannii bark extract, blood sugar levels are measured in the K+, P1, P2, and P3 groups. If blood sugar levels have increased (>128 mg/dL), the P1, P2, and P3 groups are given the Cinnamomum burmannii bark extract according to the predetermined dosage. The treatment is carried out for 14 days. On the last day, surgery is performed to extract the testes and observe the spermatozoa count. The observation data on testis weight and spermatozoa count will be analyzed using ANOVA with SPSS 24.0. The results indicate that the administration of methanol extract from Cinnamomum burmannii bark significantly affects the increase in testis weight and spermatozoa count in type-1 diabetes mellitus mice. The increase in testis weight and spermatozoa count is proportional to the dosage given